PENGGUNAAN BAHASA WANDU DALAM PROSES KOMUNIKASI ANTAR PRIBADI KALANGAN WARIA DI KECAMATAN POLEWALI - Muhammad Massyat; Muhammad Syaeba; Sri Ultifa Akbari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2018)
This study aims to find out how the use of Wandu language among waria especially in Polewali Mandar. In this study, the respondents were ten transvestites in Polewali District who had criteria determined by the author. Based on the objectives to be achieved, this study includes descriptive quality research. Descriptive research aims to describe the state or status of events. In this case to find out and explain the use of the language of Wandu in interpersonal communication among waria. The results showed that the average transvestite used the language of transvestites to communicate with other transvestites. That transvestites do so that they are more free to communicate and convey things that others do not want to know like their personal problems.